New taxa and new records of oribatid mites of the family Galumnidae (Acari: Oribatida) from Ecuador - Ermilov, Sergey G.; Starý, Josef; Sandmann, Dorothee; Marian, Franca; Maraun, Mark (Zootaxa, 2013)
The new genus Neoctenogalumna gen. nov. with Ctenogalumna moresonensis Engelbrecht, 1972 as a type species and the new subgenus Neoctenogalumna (Paractenogalumna) subgen. nov. with Neoctenogalumna (Paractenogalumna) longiciliata sp. nov. as a type species are proposed. Four new species Allogalumna ampla sp. nov., Galumna miniporosa sp. nov., Pergalumna ornamenta sp. nov. and Neoctenogalumna (Paractenogalumna) longiciliata sp. nov. are described from Ecuadorian soils. Neoctenogalumna moresonensis (Engelbrecht, 1972) comb. nov. and N. congoensis (Starý, 2005) comb. nov. are transferred in the genus Neoctenogalumna gen. nov. from Ctenogalumna. An identification key to known species of Neoctenogalumna gen. nov. is provided. An annotated checklist of identified Ecuadorian Galumnidae is presented. Four species Allogalumna borhidii Balogh & Mahunka, 1979, A. cubana Balogh & Mahunka, 1979, Pergalumna australis Pérez-Íñigo & Baggio, 1980, Galumna laselvae Balogh, 1997—are recorded for the first time from Ecuador. One genus and one species Trichogalumna Balogh, 1960 and Trichogalumna nipponica (Aoki, 1966) are recorded for the first time from the Neotropical region.